New wetland formation at the Peruvian Northern Coast: Biophysical stability and biodiversity - Díaz, Aníbal (2021)
The formation of a coastal wetland located south of Salaverry (La Libertad – Peru) is first described, analyzed, and reported, and their biodiversity is compared with regional wetlands located at coastal areas, using publically access satellite imagery and biological information. An adequate time-series was obtained to hypothesize their formation, calculating the NDVI (Normalized difference vegetation index) and NDMI (Normalized Difference Moisture Index) to confirm the stability and influence. The analysis suggests that the wetland south of Salaverry was formed fifteen years ago by two human sources: freshwater infiltration from farmlands and seawater used to pump the dredged material in the vicinity of the Salaverry Port. Because of its ecosystemic features, the wetland would be at the first stages of the ecological succession, and despite its spontaneous origin, it will be functioning as a brackish coastal lagoon attracting opportunistic fauna, mainly birds.